Reviews of Environmental Contamination and Toxicology 187 - Ware, George; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2006)
Reviews of Environmental Contamination and Toxicology attempts to provide concise, critical reviews of timely advances, philosophy and significant areas of accomplished or needed endeavor in the total field of xenobiotics, in any segment of the environment, as well as toxicological implications.
Does Pesticide Risk Assessment in the European Union Assess Long-Term Effects? -- Sulfonamides in the Environment as Veterinary Drugs -- Terminology of Gonadal Anomalies in Fish and Amphibians Resulting from Chemical Exposures -- Behavior of Pesticides in Water-Sediment Systems.
Keywords: Ecotoxicology; Applied ecology; Environment; Pollution prevention; Water pollution; Ecotoxicology; Applied Ecology; Environment, general; Industrial Pollution Prevention; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution